2021
DOI: 10.21203/rs.3.rs-274276/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sevoflurane post-conditioning alleviated hypoxic-ischemic brain injury in neonatal rats by inhibiting endoplasmic reticulum stress-mediated autophagy via IRE1 signalings

Abstract: Post-conditioning with sevoflurane, a volatile anesthetic, has been proved to be neuroprotective against hypoxic-ischemic brain injury (HIBI). Our previous research showed that autophagy is over-activated in a neonatal HIBI rat model, and inhibition of autophagy confers neuroprotection. There is increasing recognition that autophagy can be stimulated by activating endoplasmic reticulum (ER) stress. Herein, we purposed to explore: i) the association of ER stress with autophagy in the setting of neonatal HIBI; a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Sevo urane is commonly used as an inhalation anesthetic in the clinic. Sevo urane postconditioning has increasingly been studied in recent years for its neuroprotective effects [16][17][18]. In several studies, postconditioning with sevo urane was demonstrated to protect against cerebral I/R-induced damage.…”
Section: Introductionmentioning
confidence: 99%
“…Sevo urane is commonly used as an inhalation anesthetic in the clinic. Sevo urane postconditioning has increasingly been studied in recent years for its neuroprotective effects [16][17][18]. In several studies, postconditioning with sevo urane was demonstrated to protect against cerebral I/R-induced damage.…”
Section: Introductionmentioning
confidence: 99%